The role and clinical significance of tumor-associated macrophages in the epithelial–mesenchymal transition of lung cancer - Liao, Lei; Wang, Ying-Xia; Fan, Su-Su; Hu, Ying-Yue; Wang, Xue-Chang; Zhang, Xuan (Frontiers in Oncology, 2025)
Lung cancer remains the leading cause of cancer-related mortality worldwide. Tumor-associated macrophages (TAMs) and epithelial-mesenchymal transition (EMT) are key drivers of lung cancer metastasis and drug resistance. M2-polarized TAMs dominate the immunosuppressive tumor microenvironment (TME) and promote EMT through cytokines such as TGF-β, IL-6, and CCL2. Conversely, EMT-transformed tumor cells reinforce TAM recruitment and M2 polarization through immunomodulatory factors such as CCL2 and ZEB1, thereby establishing a bidirectional interplay that fuels tumor progression. Current evidence on this interaction remains fragmented, and a comprehensive review of the TAM-EMT regulatory network and its therapeutic implications is lacking. This review systematically integrates the bidirectional regulatory mechanisms between TAMs and EMT, highlighting their roles in lung cancer progression. It also summarizes emerging therapeutic strategies targeting TAM polarization and the EMT process, emphasizing their potential for clinical translation. This study fills the gap in systematic reviews on the interaction between TAMs and EMT, providing a comprehensive theoretical foundation for future research and the development of novel lung cancer therapies.